Homogenisation approaches for structural analysis of masonry buildings - Lourenço, Paulo B. (2006)
Modern methodologies for the conservation of architectural heritage require structural analysis for the purpose of diagnosis and safety evaluation. This is not an easy task, as masonry structures usually feature a very low tensile strength, thus rendering the tool usually adopted for design of new structures (linear elastic analysis) of very limited use. Non-linear analysis of ancient masonry structures is a popular field in masonry research and homogenisation techniques play presently a major role, despite the mathematical and conceptual difficulties inherent to the approach. The paper addresses different homogenisation techniques available in the literature, with a focus on micro-mechanical models and on the polynomial expansion of the stress field. These seem promising and accurate strategies for advanced structural analysis.